2009
DOI: 10.1677/jme-08-0151
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of urocortin I and its related peptide urocortin II by inflammatory and oxidative stresses in HL-1 cardiomyocytes

Abstract: Despite our knowledge on the regulation of urocortin (Ucn) I and its related peptides in the heart, the possible involvement of cardiovascular stress substances, such as cytokines or angiotensin II (Ang II), on this regulation remains to be fully elucidated. We therefore evaluated the potential role of cardiovascular stress substances on the regulation of the Ucn-corticotropin-releasing hormone (CRH) receptor system in HL-1 cardiomyocytes using a Ucn I-specific RIA, conventional reverse transcription-PCR (RT-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…However, other reports showed that glucocorticoids downregulated Ucn 2 expression in the skin and upregulated its expression in the hypothalamus or brain stem (12,13), supporting a tissuespecific glucocorticoid regulation of Ucn 2 as reported for Ucn 1 (30) that needs to be delineated specifically in the stomach. Other mechanisms may involve LPS-related release of cytokines and oxidative stress as demonstrated in Ucn 1 and Ucn 2 gene upregulation by LPS in HL-1 cardiomyocytes (28).…”
Section: Regulation Of Gc Ucn/crf 2 System By Low Dose Of Endotoxinmentioning
confidence: 99%
“…However, other reports showed that glucocorticoids downregulated Ucn 2 expression in the skin and upregulated its expression in the hypothalamus or brain stem (12,13), supporting a tissuespecific glucocorticoid regulation of Ucn 2 as reported for Ucn 1 (30) that needs to be delineated specifically in the stomach. Other mechanisms may involve LPS-related release of cytokines and oxidative stress as demonstrated in Ucn 1 and Ucn 2 gene upregulation by LPS in HL-1 cardiomyocytes (28).…”
Section: Regulation Of Gc Ucn/crf 2 System By Low Dose Of Endotoxinmentioning
confidence: 99%
“…MP-1 interacts specifically with MEK1 and ERK1, enhances their interaction and recruits these complexes to late endosomes. MP-1 complex is anchored to the endosomal membrane by means of binding to the late-endosomal resident proteins, p14 and p18 [14]. Loss of individual components of the MP-1/p14/p18 complex reduces duration of the ERK1/2 activity, thus implicating late endosomes as an important platform for the ERK1/2 signaling [15].…”
Section: Introductionmentioning
confidence: 99%
“…From an evolutionary perspective, UCNII belongs to one of the oldest peptide lineages conserved between species and regulates stress responses in endocrine, autonomic and immune systems (49, 50). Beside UCNIII, UCNII is the unique member of the CRH family that possesses structural features that are present in the single CRH-like peptide of tunicates and in the insect diuretic peptide (51).…”
Section: Discussionmentioning
confidence: 99%